4Cs of finance applications: cash, collateral, character and capability. Issue 4 (7th May 2021) - Ejdelbaum, Henry
Abstract : The bespoke nature of business finance means that any business that is looking to raise funds might face certain challenges. As lenders underwrite all the different aspects of each individual application and have their own criteria and guidelines, it can sometimes be tricky to raise finance for a business. Fortunately, the nature of veterinary practice businesses means that there are several aspects of the industry that are usually advantageous to any finance application.